2014
DOI: 10.5152/tjar.2014.06025
|View full text |Cite
|
Sign up to set email alerts
|

Post-Laparoscopic Cholecystectomy Pain: Effects of Preincisional Infiltration and Intraperitoneal Levobupivacaine 0.25% on Pain Control-a Randomized Prospective Double-Blinded Placebo-Controlled Trial

Abstract: Objective: The aim of this study was to compare the postoperative analgesic efficacy of preincisional and intraperitoneal levobupivacaine or normal saline in patients undergoing laparoscopic cholecystectomy. Methods:Sixty patients who participated in the study were randomly divided into 3 groups. Group 1 received intraperitoneal levobupivacaine (0.25% 40 mL) immediately after the pneumoperitoneum. Group 2 received periportal levobupivacaine (0.25% 5 mL in each trochar incision area) before incision and intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…who reported the analgesic effects of intraperitoneal levobupivacaine for laparoscopic cholecystectomy and found that it is an effective method for decreasing pain after laparoscopic cholecystectomy and reducing antiemetic drug taking. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…who reported the analgesic effects of intraperitoneal levobupivacaine for laparoscopic cholecystectomy and found that it is an effective method for decreasing pain after laparoscopic cholecystectomy and reducing antiemetic drug taking. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…compared the effects of the combination of preincision infiltration of trocar sites plus intraperitoneal instillation of levobupivacaine 0.25% after pneumoperitoneum with intraperitoneal instillation alone for postoperative pain management following laparoscopic cholecystectomy and found that either the combination or intraperitoneal instillation of LA alone reduced the shoulder pain significantly than the control group. [ 8 ] Similarly, Louizos et al . also observed that this combination was better than other groups as well as the control group.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have analyzed the efficacy of combined trocar site infiltration and intraperitoneal instillation of LA and the results are conflicting. [ 8 9 10 ] Karaman et al . compared the effects of the combination of preincision infiltration of trocar sites plus intraperitoneal instillation of levobupivacaine 0.25% after pneumoperitoneum with intraperitoneal instillation alone for postoperative pain management following laparoscopic cholecystectomy and found that either the combination or intraperitoneal instillation of LA alone reduced the shoulder pain significantly than the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] There are some studies that propose that preincisional analgesic infiltration can delay the first analgesic requirement in the postoperative period. [ 11 12 ] With this background the present study was carried out with an aim to evaluate and compare the postoperative pain relief in AH patient under general anesthesia after preincisional versus postincisional infiltration of surgical area with Bupivacaine. The dose selection of Bupivacaine was done keeping in view the previous studies that have reported up to 50 mL of 0.25% to 0.375% Bupivacaine infused subcutaneously to be safe and effective in the management of postoperative pain in AH or other major abdominal surgery cases.…”
Section: Discussionmentioning
confidence: 99%